2023
DOI: 10.7196/samj.2023.v113i6.16765
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic joint infection:A South African perspective

Abstract: Background. South African data on the bacteriology and sensitivity profile of periprosthetic joint infection is lacking.  Current regimens for systemic and local antibiotic therapy are based on international literature. These regimens are different for the United States of America and Europe and might thus not be relevant to South Africa. Objectives.  To determine the characteristics of periprosthetic joint infection in a South African clinical setting by identifying the most common organisms cultured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…On the other hand, this study complied with the standard aspiration procedures practiced at our clinic, which made it possible to collect accurate patient data. Current studies show that Staphylococcus was the most frequently detected organism according to the microbiological profile of both preoperative aspiration and intraoperative cultures in patients with knee and hip PJI [25][26][27][28][29]. Moreover, Propionibacterium acnes was the most commonly reported microorganism in studies investigating PJI of the shoulder [30][31][32].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, this study complied with the standard aspiration procedures practiced at our clinic, which made it possible to collect accurate patient data. Current studies show that Staphylococcus was the most frequently detected organism according to the microbiological profile of both preoperative aspiration and intraoperative cultures in patients with knee and hip PJI [25][26][27][28][29]. Moreover, Propionibacterium acnes was the most commonly reported microorganism in studies investigating PJI of the shoulder [30][31][32].…”
Section: Discussionmentioning
confidence: 98%
“…According to the authors, such a recommendation is to ensure coverage of the widest possible spectrum, and thus to ensure the maximum possible effectiveness of eradication of the infection. They also emphasize the difference between the recommended treatment in PJI and the American or European guidelines [ 138 ]. Pecora JR et al, from Sao Paulo, Brazil, indicated that to preserve the joint prosthesis, a broad-spectrum antibiotic should be used based on hospital microbial profiles, and surgical debridement should be used to identify the causative factor and initiate targeted therapy immediately.…”
Section: Antibiotic Therapymentioning
confidence: 99%